Branching (tillering) in the plant of the (cereals) such as bread wheat (Triticum eastivum L.) and barley (Hordeum vulgare L.) - ZEDDIG, houda; BENLARIBI, mostefa (Journal of agricultural, environmental and veterinary sciences, 2017)
Two genotypes of  wheat (Triticum estivum L.)  Mahon demias , Mexipak and two genotypes of barley  (Hordeum vulgare L.) Rihane and Saida , were studied in the vitreous house of the D.V.R.P laboratory at the University of Brothers Mentouri Constantine 1 (Algeria) , the anatomical study was performed in stage 4 leaves ( 4L) in the Tillering tray  using the manual method and then coloring  the sections with the carmine-green ,  observations under light microscope showed a variation in species in both varieties and in both genus : Mahon demias in bread  wheat was formed 4 tillers buds , while Mexipak in bread wheat was formed  3 tillers buds , while Saida gave only two buds  with the observation that barley was early in the composition compared to bread wheat.
Keywords: Anatomy; Bud; Tillering; Triticum eastivum L. , Hordeum vulgare L.